Antioxidant properties of certain C5 substituted 4-arylimino-thiazolidin-2-ones - Z.I. Chulovska (Danylo Halytsky Lviv National Medical University, 2020)
Aim. Expanding the synthetic potential of 4-arylimino-thiazolidin-2-ones; a study of reactivity; and primary screening for antioxidant activity of synthesized compounds.